The impact of pulsatile vs. non-pulsatile perfusion in patients undergoing cardiopulmonary bypass: A comprehensive systematic review and meta-analysis of 33 randomized controlled trials - Mohamed R. Abdelraouf; Abdelrahman Mahmoud; Ahmed Mazen Amin; Hazem Mohamed Salamah; Hassan Alshaker; Hazem Rezq; Ali Ashraf Salah Ahmed; Mohamed Ahmed Ali; Abdallah Saeed; Majd M. AlBarakat; Dina Ayman; Salem Elshenawy; et al. (PLoS ONE, 2025)
Background Pulsatile perfusion is a developing technique that attempts to mimic the natural pulsatile flow of blood during cardiopulmonary bypass (CBP). Purpose This systematic review and meta-analysis was conducted to show the effects of pulsatile perfusion in CPB compared to non-pulsatile. Methods Randomized control trials that evaluated the implementation of pulsatile perfusion during cardiopulmonary bypass surgery were identified by a literature search in the following electronic databases (PubMed, Web of Science, Scopus, CENTRAL, and Embase) published from inception up to February 2024. Results The search yielded 33 trials of which three studies demonstrated a low risk of bias, 29 studies showed some concerns, and one study presented a high risk of bias overall. The total number of patients was 3174 patients. The analysis showed that pulsatile perfusion led to a significant decrease in creatinine level [MD = −0.14, 95% CI (−0.24, −.04), P < 0.004], lactate level [MD = −8.21, 95% CI (−13.16, −3.25), P < 0.001], hospital stay [MD = −1.38, 95% CI (−2.51, −0.25), P = 0.016], ICU stay [MD = −0.47, 95% CI (−0.82, −0.13), P = 0.007], intubation time [MD = −3.73, 95% CI (−5.42, −2.04), P < 0.001], and increase in creatinine clearance [MD = 10.08, 95% CI (3.36, 16.80), P < 0.003]. However, no significant difference between the two regimens was detected in estimated glomerular filtration rate (eGFR), alanine transferase (ALT) level, AST (aspartate transferase) level, Blood urea nitrogen (BUN) level, acute renal failure (ARF), and mortality rates. Conclusion Pulsatile perfusion showed some positive effects on creatinine, creatinine clearance, lactate level, hospital stay, ICU stay, and intubation time. However, there was no difference between the two methods on BUN, ALT, AST, eGFR, ARF, and death. Most of the outcomes showed significant heterogeneity, which requires more robust RCTs to be conducted to increase the quality and the certainty of evidence.